2020
DOI: 10.3390/en13153892
|View full text |Cite
|
Sign up to set email alerts
|

Interface Damages of Electrical Insulation in Factory Joints of High Voltage Submarine Cables

Abstract: As a key accessory of high-voltage (HV) insulated submarine cable, the factory joints of the cross-linked polyethylene (XLPE) represent an unpredictable uncertainty in cable-connecting fabrications by means of the extruded molding joint (EMJ) technique. The electrical breakdown pathways formed at the interfaces between recovery insulation and cable body under alternative current 500 kV voltages are specifically investigated by microstructure characterizations in combination with the electric field and fractal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The applied voltage is firstly raised up to 2.5 kV by a rate of 0.1 kV s −1 and persisted for 15 min, then continuously increased at the rate of 0.1 kV s −1 until electricaltree appears. 19 A polarizing fluorescence microscope (PLM, DM2500P, Leica Co., Berlin, Germany) under normal mode, which is equipped with a charge-coupled device (CCD) camera connecting computer interface, is utilized to in situ observe electrical-tree growth (inception and propagation), in which 10 μm tree-length is specified as the inception of electrical-tree ageing. For each material, 10 samples are tested to be analyzed in two-parameter Weibull statistics.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The applied voltage is firstly raised up to 2.5 kV by a rate of 0.1 kV s −1 and persisted for 15 min, then continuously increased at the rate of 0.1 kV s −1 until electricaltree appears. 19 A polarizing fluorescence microscope (PLM, DM2500P, Leica Co., Berlin, Germany) under normal mode, which is equipped with a charge-coupled device (CCD) camera connecting computer interface, is utilized to in situ observe electrical-tree growth (inception and propagation), in which 10 μm tree-length is specified as the inception of electrical-tree ageing. For each material, 10 samples are tested to be analyzed in two-parameter Weibull statistics.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Electric-tree propagation is derived from structural damage caused by partial discharge at the distorted electric field near electric-tree tip, so the addition of aromatic ketone compound as a voltage stabilizer into polymer materials can inhibit electron impact ionization caused by partial discharge in air gaps by trapping or scattering hot charge carriers. 26 Chemical modifications of grafting AOHBP and VPE achieve a significant improvement in electric-tree resistance, as indicated by the complete increase of extension coefficients at every aging time. In particular, the remarkably higher extension coefficients of AOHBP/EPDM than that of VPE/EPDM indicate that AOHBP is preferred rather than VPE for improving electric-tree resistant performance.…”
Section: First-principles Calculation Schemes Specificationsmentioning
confidence: 99%
“…The results show that the electrical tree morphology of the samples in the interface transition area has the characteristic of not growing along the direction of the electric field, and its electrical tree starting voltage is lower than that of the main body samples. 22 Wang et al investigated the development process of the electrical tree discharge between the layers of epoxy resinimpregnated paper. The results showed that the development process of the electrical tree discharge went through the initial, growth, stagnation, and rapid development stages, in which the suppression of space charge in the stagnation stage reduces the rate of forward extension of the main path of the electrical tree.…”
Section: ■ Introductionmentioning
confidence: 99%